Examining user thermal comfort in spaces between buildings: Exploring parametric solutions for BIPVs for Luleå, Sweden, and Limassol, Cyprus - Savvides, Andreas; Vassilliades, Constantinos; Lau, Kevin; Rizzo, Agatino (Energy Reports, 2024)
The global concern over the interplay between climate mitigation, urban structures, and city energy usage underscores a pressing need for innovative solutions. This research delves into the relationship between urban layouts, energy dynamics, and the thermal comfort of public spaces between buildings. Focusing on the contrasting climates of Luleå, Sweden, and Limassol, Cyprus, the study employs ENVI-met, a microscale urban climate simulation tool, for a parametric exploration at the city block scale. Assessing eight distinct scenarios across morning, noon, and afternoon timeframes, the research considers the impact of Building-Integrated Photovoltaics (BIPVs) on user thermal comfort. Contrary to expectations, the study reveals that BIPV integration alone may not be the primary driver of improved thermal comfort during peak heat periods. Instead, factors like urban density and urban morphology emerge as influential contributors. For instance, increasing the urban fabric density by doubling the building height resulted in greater PET fluctuations ranging from −3 to +3 degrees, compared to the modest PET fluctuations ranging from 0 to +3 degrees observed with the simple integration of PVs onto buildings. These findings offer valuable insights for urban planners and policymakers, guiding decisions in considering the issue of thermal comfort in public spaces between buildings, while optimizing energy consumption in urban areas. Validerad;2024;Nivå 2;2024-08-12 (hanlid); Full text license: CC BY-NC-ND